2020
DOI: 10.1029/2019jg005261
|View full text |Cite
|
Sign up to set email alerts
|

Multimodel Evaluation of Nitrous Oxide Emissions From an Intensively Managed Grassland

Abstract: Process-based models are useful for assessing the impact of changing management practices and climate on yields and greenhouse gas (GHG) emissions from agricultural systems such as grasslands. They can be used to construct national GHG inventories using a Tier 3 approach. However, accurate simulations of nitrous oxide (N 2 O) fluxes remain challenging. Models are limited by our understanding of soil-plant-microbe interactions and the impact of uncertainty in measured input parameters on simulated outputs. To i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…For N 2 O emissions, relative biases were −0.80-0.03 and RRMSE ranged between 0.13 and 0.81 (Ehrhardt et al, 2018; see Table S1a). A detailed validation of N 2 O emissions and its drivers at the Swiss site revealed that both models used here generally performed better than the Swiss IPCC calculations for that site (Fuchs et al, 2020).…”
Section: Validation Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…For N 2 O emissions, relative biases were −0.80-0.03 and RRMSE ranged between 0.13 and 0.81 (Ehrhardt et al, 2018; see Table S1a). A detailed validation of N 2 O emissions and its drivers at the Swiss site revealed that both models used here generally performed better than the Swiss IPCC calculations for that site (Fuchs et al, 2020).…”
Section: Validation Resultsmentioning
confidence: 87%
“…In order to obtain the response variables on a homogeneous grid and exclude inter-annual variability, surfaces were fitted to model outputs (yield, N 2 O emissions) per model-site combination on the surface expanded by actual clover percentage and annual fertilizer amount. Ehrhardt et al, 2018) with respect to plant productivity, soil moisture and temperature, soil mineral N content, and model uncertainties of the respective models were evaluated in an international model intercomparison (Ehrhardt et al, 2018 ; Table S1) with further testing of yield and N 2 O emissions at two levels of pasture clover content in Fuchs et al (2020). Biological nitrogen fixation and yields in grass-clover mixtures were validated at one site described by Fitton et al (2019).…”
Section: Models Used In This Studymentioning
confidence: 99%
See 2 more Smart Citations
“…The study by further elaborated the variation in management intensity and related variations in GHG exchange across sites, stressing the need for more case studies based on continuous GHG observations to improve existing knowledge and close remaining knowledge gaps. To complete the picture on factors driving ecosystem GHG exchange, irregularly occurring events such as dry spells or extraordinary wet periods can further lead to enhanced or reduced GHG emissions (Chen et al, 2016;Hartmann and Niklaus, 2012;Hopkins and Del Prado, 2007;Mudge et al, 2011;Wolf et al, 2013).…”
Section: Introductionmentioning
confidence: 99%